Measuring Variation in Use of the WHO Surgical Safety Checklist in the Operating Room: A Multicenter Prospective Cross-Sectional Study. - Russ, S; Rout, S; Caris, J; Mansell, J; Davies, R; Mayer, E; Moorthy, K; Darzi, A; Vincent, C; Sevdalis, N (Elsevier, 2015)
BACKGROUND: Full implementation of safety checklists in surgery has been linked to improved outcomes and team effectiveness; however, reliable and standardized tools for assessing the quality of their use, which is likely to moderate their impact, are required. STUDY DESIGN: This was a multicenter prospective study. A standardized observational instrument, the "Checklist Usability Tool" (CUT), was developed to record precise characteristics relating to the use of the WHO's surgical safety checklist (SSC) at "time-out" and "sign-out" in a representative sample of 5 English hospitals. The CUT was used in real-time by trained assessors across general surgery, urology, and orthopaedic cases, including elective and emergency procedures. RESULTS: We conducted 565 and 309 observations of the time-out and sign-out, respectively. On average, two-thirds of the items were checked, team members were absent in more than 40% of cases, and they failed to pause or focus on the checks in more than 70% of cases. Information sharing could be improved across the entire operating room (OR) team. Sign-out was not completed in 39% of cases, largely due to uncertainty about when to conduct it. Large variation in checklist use existed between hospitals, but not between surgical specialties or between elective and emergency procedures. Surgical safety checklist performance was better when surgeons led and when all team members were present and paused. CONCLUSIONS: We found large variation in WHO checklist use in a representative sample of English ORs. Measures sensitive to checklist practice quality, like CUT, will help identify areas for improvement in implementation and enable provision of comprehensive feedback to OR teams.